Epidemiologia da malária em Coari, Amazônia Brasileira, entre 2004-2008 - (:unkn) unknown (Universidade Federal do Amazonas, 2010)
Malaria is an infectious and parasitic disease of major socio-economic repercussions worldwide. In Brazil, 99% of cases are in the Amazon region, where highlights of the city of Coari with 5.7% of reported cases in the state of Amazonas. This quantitative study was retrospective, descriptive of the behavior of malaria in the municipality of Coari-AM from 2004 to 2008, used secondary data collected from medical records and databases, analyzed using Epi-info. The highest incidence rate was lower in 2007 and 2004. The predominant type of plasmodium vivax in the study period. Most cases occurred in males and between 20-29 years. There were 87 hospitalizations during the study period. The only record of death from malaria was in 2007. The Coari-Manaus led workers exposure to the disease. The increase in cases of vivax malaria require specific measures. And young males are more exposed at times prone to infection by the disease. There was a lot of underreporting and reduced hospitalization rates.
Keywords: epidemiologia; malária; sistemas de informação; epidemiology; information systems; CIÊNCIAS DA SAÚDE